L-Lift Technique Using Poly-L-Lactic Acid: A Pilot Study. Issue 8 (August 2021) - Hexsel, Doris; Camozzato, Fernanda; Valente-Bezerra, Indira; Silva, Aline F.; Siega, Carolina
Abstract : BACKGROUND: Minimally invasive procedures that prevent and delay the aging process can be an alternative to more invasive surgical procedures. OBJECTIVE: To assess the efficacy and safety of L-Lift technique to improve skin firmness, facial global aesthetics, and the patient and investigator satisfaction. METHODS: Prospective, open, single-center study. Thirty participants underwent 3 treatment sessions 1 month apart and were assessed 8, 16, and 24 weeks after first injections. Assessments included the Facial Laxity Rating Scale (FLRS), Global Aesthetic Improvement Scale (GAIS), objective measurement of skin elasticity, and the Skin Distension Test. RESULTS: At Week 24, 60% of the patients had at least 1-class improvement in the FLRS for the middle face and 33% for the lower face. At Week 24, investigators considered that 90.0% of the patients improved according to the GAIS and 90.0% of the subjects considered they have improved. Skin elasticity (at Week 8 and at Week 16) and Skin Distension Test (at Week 24) assessments indicated improvement in skin firmness. Both patients and investigators were satisfied with the treatment at the study end. CONCLUSION: The technique is safe and efficacious. It may be particularly suitable for patients presenting initial signs of facial skin laxity.